Crime and Self-Control Revisited: Disentangling the Effect of Self-Control on Risk and Social Preferences - Tim Friehe; Hannah Schildberg-Hörisch (Institute for the Study of Labor (IZA), 2014)
In economic models, risk and social preferences are major determinants of criminal behavior. In criminology, low self-control is considered a fundamental cause of crime. Relating the arguments from both disciplines, this paper studies the relationship between self-control and both risk and social preferences. To exogenously vary the level of self-control, we use a well-established experimental manipulation. We find that low self-control causes less risk-averse behavior. The effect of self-control on social preferences is not significant. In sum, our findings support the proposition that low self-control is a facilitator of crime. While our study is motivated by the literature on the determinants of criminal behavior, it has important implications for dual-system models and documents endogeneity of economic preferences.
Keywords: K42; H23; C91; 330; criminal behavior; risk preferences; social preferences; ego-depletion; dual-system models; experiment; endogeneity of economic preferences